An Explanation for the Current Sex Distribution in the Riverside Cemetery (20ME01), a Terminal Archaic Site, and Implications for a Possible Site Reinterpretation - (:unkn) unknown (My University, 2020)
Current research on the Riverside Cemetery (20ME01), a hypothesized Terminal Archaic site in Menominee County in the Upper Peninsula of Michigan, has focused on the rise in hunter-gatherer social complexity from the Middle to Late Archaic through the analyses of copper use and function in burial contexts. This article is a step in the preliminary research for a Masters thesis that will reexamine the burial context at Riverside. This is a proposal for eliminating the present ethnocentric perspective directing current interpretations of the Riverside Cemetery as being a correlate of a male-dominated hierarchical society. I propose that the Riverside Cemetery is a correlate of an egalitarian society in which a division of labor, by sex and age, is the functioning unit for subsistence survival. Support for this reinterpretation is highlighted by the burial context and corresponding ethnohistoric accounts of Ojibwe populations inhabiting the Western Great Lakes region. Furthermore, skeletal analyses and examination of burial features accentuate the dietary lifestyle characteristic of the proposed subsistence culture.
Keywords: Riverside Cemetery (20ME01); Michigan Archaeology; Late/Terminal Archaic; Red Ochre; Western Great Lakes Archaeology; Mortuary Analysis; Subsistence; Ojibwe